Defining ecologically relevant water quality targets for lakes in Europe. Issue 3 (11th March 2014) - Poikane, Sandra; Portielje, Rob; van den Berg, Marcel; Phillips, Geoff; Brucet, Sandra; Carvalho, Laurence; Mischke, Ute; Ott, Ingmar; Soszka, Hanna; Van Wichelen, Jeroen; Strecker, Angela
Summary The implementation of the Water Framework Directive requires EU member states to establish and harmonize ecological status class boundaries for biological quality elements. In this paper, we describe an approach for defining ecological class boundaries that delineates shifts in lake ecosystem functioning and, therefore, provides ecologically meaningful targets for water policy in Europe. We collected an extensive data set of 810 lake‐years from nine Central European countries, and we used phytoplankton chlorophyll a, a metric widely used to measure the impact of eutrophication in lakes. Our approach establishes chlorophyll a target values in relation to three significant ecological effects of eutrophication: the decline of aquatic macrophytes, the dominance of potentially harmful cyanobacteria and the major functional switch from a clear water to a turbid state. Ranges of threshold chlorophyll a concentrations are given for the two most common lake types in lowland Central Europe: for moderately deep lakes (mean depth 3–15 m), the greatest ecological shifts occur in the range 10–12 μg L−1 chlorophyll a, and for shallow lakes (<3 m mean depth), in the range 21–23 μg L−1 chlorophyll a. Synthesis and applications. Our study provides class boundaries for determining the ecological status of lakes, which have robust ecological consequences for lake functioning and which, therefore, provide strong and objective targets for sustainable water management in Europe. The results have been endorsed by all participant member states and adopted in the European Commission legislation, marking the first attempt in international water policy to move from physico‐chemical quality standards to harmonized ecologically based quality targets.